Proceedings of the 3rd International Conference Entitled Language, Literary, and Cultural Studies, ICON LATERALS 2022, 05–06 No 2023
DOI: 10.4108/eai.5-11-2022.2329483
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges of Indonesian EFL Students in Translating Indonesian Texts into English

Abstract: This article addresses the importance of grammar competence in translation studies. It aims to identify and describe the needs and problems of students in grammatical competence. By using a combination of quantitative and qualitative-descriptive research, the data cover grammar competence including thirteen elements: parts of speech, sentence elements, sentence patterns, verb tenses, subject verb agreements, sentence varieties, sentence forms, conjunctions and prepositions, sentence faults, collocations, mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Raising EFL students' competence in using mechanics such as spelling in their written paragraphs is vital to improving textual readability (Sukaesih, 2023). The current research results revealed that most level nine students thought spelling was the most important aspect.…”
Section: Quantitative Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Raising EFL students' competence in using mechanics such as spelling in their written paragraphs is vital to improving textual readability (Sukaesih, 2023). The current research results revealed that most level nine students thought spelling was the most important aspect.…”
Section: Quantitative Discussionmentioning
confidence: 65%
“…Even if students' errors in mechanics do not drastically affect the overall understanding of paragraphs, they would at least influence the quality of the written paragraphs (Yuliawati, 2021). Therefore, increasing EFL students' competence in using mechanics in their writing is crucial to improve the readability of the provided text (Sukaesih, 2023). To achieve this, EFL learners must realize the influential role of mechanics in giving meaning to their writing.…”
Section: Vocabularymentioning
confidence: 99%